Small efforts to achieve a big thing: Crime Prevention in Ibero-America - Lim, Hyeyoung (International journal of comparative and applied criminal justice, 2022)
Crime prevention in Ibero-America countries has not been well known to global criminal justice communities. This special issue provides a space that introduces, shares, and explores efforts and practices of crime prevention in Ibero-America countries as well as enlarging the existing literature on the subject. In this special issue, all contributors from around the world and from different disciplines provide valuable empirical studies to examine and evaluate crime prevention efforts in Ibero-American countries. Our work here, to construct this special issue, is a small effort, however, we hope that this small effort inspires other efforts and together we can achieve a big thing.